2020
DOI: 10.1029/2019jb018656
|View full text |Cite
|
Sign up to set email alerts
|

Urban Seismic Site Characterization by Fiber‐Optic Seismology

Abstract: Accurate ground motion prediction requires detailed site effect assessment, but in urban areas where such assessments are most important, geotechnical surveys are difficult to perform, limiting their availability. Distributed acoustic sensing (DAS) offers an appealing alternative by repurposing existing fiber‐optic cables, normally employed for telecommunication, as an array of seismic sensors. We present a proof‐of‐concept demonstration by using DAS to produce high‐resolution maps of the shallow subsurface wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 56 publications
(103 reference statements)
4
58
0
Order By: Relevance
“…This series of experiments have shown that signal quality is often good enough for earthquake detection and imaging even though loose cables in underground conduits only couple to the surrounding soils through friction and gravity (Lindsey et al, 2017;Jousset et al, 2018;Martin et al, 2019;Yu et al, 2019;Ajo-Franklin et al, 2019). At the Stanford Fiber Optic Seismic Observatory, Rayleigh wave dispersion showed significant spatial variability at scales relevant to earthquake ground motion prediction (Martin, 2018;Spica et al, 2020), and time-lapse changes through a building excavation (Fang et al, 2020). However, investigation of near-surface time-lapse changes due to seasonal precipitation variation yielded no significant velocity variation when investigated with time-lapse ambient noise interferometry (Martin, 2018).…”
mentioning
confidence: 99%
“…This series of experiments have shown that signal quality is often good enough for earthquake detection and imaging even though loose cables in underground conduits only couple to the surrounding soils through friction and gravity (Lindsey et al, 2017;Jousset et al, 2018;Martin et al, 2019;Yu et al, 2019;Ajo-Franklin et al, 2019). At the Stanford Fiber Optic Seismic Observatory, Rayleigh wave dispersion showed significant spatial variability at scales relevant to earthquake ground motion prediction (Martin, 2018;Spica et al, 2020), and time-lapse changes through a building excavation (Fang et al, 2020). However, investigation of near-surface time-lapse changes due to seasonal precipitation variation yielded no significant velocity variation when investigated with time-lapse ambient noise interferometry (Martin, 2018).…”
mentioning
confidence: 99%
“…At lower frequencies, Ajo-Franklin et al (2019) observed the surface waves from large teleseismic earthquakes, and Lindsey et al (2020) demonstrated how to convert DAS records into broadband seismograms via a comparative analysis of DAS and seismometer signals in 1-120 s range. Further applications for subsurface structural investigations have been proposed, such as receiver function (Yu et al 2019) and H/V spectral ratio (Spica et al 2020a) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using DAS arrays deployed in urban environments have reported that near-surface velocities can be estimated with ambient noise recorded by DAS over monthlong periods (Dou et al, 2017;Martin et al, 2018;Spica et al, 2019). Averaging over long observation times is needed to suppress strong near-field anthropogenic noise but severely limits the temporal resolution of passive seismic monitoring with DAS.…”
Section: Introductionmentioning
confidence: 99%